Complex systems design & management : proceedings of the seventh International Conference on Complex Systems Design & Management, CSD & M Paris 2016 /: proceedings of the seventh International Conference on Complex Systems Design & Management, CSD & M Paris 2016. (2017) - Unknown
No abstract available